A Perennial Problem: Employment, Joblessness and Poverty - Saunders, P (The Social Policy Research Centre, 2006)
Employment and poverty have been at the forefront of economic and social policy debate for most of the last three decades. Although the emphasis has changed (as has the language), the idea that unemployment is the principal cause of poverty among those of workforce age has been a central finding of poverty research. However, this has had far too little impact on those who set policy – particularly economic policy. The result has been a widening gap between the achievements of economic policy and the problems confronting social policy. Despite the rhetoric, Australian policy-makers have been unwilling to develop the ideas and commit the resources required to eradicate poverty, except as a by-product of the achievement of other goals.
Social Polciy Research Centre
Keywords: Income & Finance -- Poverty and disadvantage; Employment -- Unemployment; Policy; Income, wealth and finances; Labour market; Government, law and policy; Employment; Policy; Income & Finance; Unemployment; Poverty and disadvantage; Income, wealth and finances; Employment and unemployment; Government, law and policy